Relation of Blood Pressure and Body Mass Index During Childhood to Cardiovascular Risk Factor Levels in Young Adults - Rademacher, Erin R. (2009)
INTRODUCTION: Adult obesity and hypertension are leading causes of cardiovascular morbidity/mortality. Although childhood body mass index and blood pressure track into adulthood, how they influence adult cardiovascular risk independent of each other is not well defined. METHODS: Participants were from two longitudinal studies with a baseline evaluation at mean age 13 and a follow-up at mean age 24. Regression models using childhood blood pressure and body mass index to predict young adult cardiovascular risk factors were performed. RESULTS: In univariate analysis, childhood body mass index predicted young adult blood pressure, lipids, glucose, insulin, and insulin resistance, while childhood blood pressure predicted young adult blood pressure, lipids and glucose. In a multivariable regression model (adjusted for age, sex and race) which included change in body mass index and blood pressure from age 13 to 24, body mass index predicted all young adult risk factors except blood pressure and glucose. Baseline systolic blood pressure predicted young adult blood pressure, cholesterol, triglycerides and glucose while baseline diastolic blood pressure predicted young adult blood pressure, body mass index and glucose. CONCLUSIONS: The results from this study show that 1) blood pressure and body mass index act independently in children to influence future cardiovascular risk factors, and 2) the combination of high blood pressure and body mass index in childhood have an additive effect in predicting the highest levels of young adult cardiovascular risk. Thus, there should be a focus on treating hypertension in overweight and obese children, in addition to attempting to reduce weight.